The Effect of Profitability, Capital Structure, Company Size, Dividend Policy on Firm Value: A Comparative Study on the Consumer Cyclical and Non-Cyclical on the IDX - Afiyah Alimah Salsabila; Imronudin Imronudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Indonesian companies often face low firm value, driven by profitability, capital structure, firm size, and dividend policy, with sectoral differences shaping market responses. This study aims to analyze the effect of profitability (ROA), capital structure (DER), firm size (FS), and dividend policy (DPR) on firm value (Tobin’s Q) in consumer cyclical and non-cyclical companies listed on the Indonesia Stock Exchange in 2024. The research employs a quantitative approach using multiple linear regression analysis with purposive sampling techniques. The results show that profitability has a positive and significant effect on firm value in both sectors. Capital structure exerts a significant negative effect in the cyclical sector but a significant positive effect in the non-cyclical sector. Firm size consistently has a significant negative impact on firm value in both sectors. Meanwhile, dividend policy does not have a significant effect on firm value. These findings highlight the importance of sectoral characteristics in assessing firm value and suggest that investors in Indonesia’s capital market place greater emphasis on profitability and capital structure considerations rather than dividend distribution.